Mesiodistal values of permanent frontal teeth crown of german shepherd (VETERINARIA, 2020)
A study of mesiodistal crown values of permanent frontal teeth and their relationship in the jaws was performed on 10 German Shepherd dogs, 1-10 years ofage, who belong to a group of lupoid or mesocephalic head type. Study material was taken after the autopsy examination of dead dogs, which was conducted at the Department of Veterinary Pathology, University of Sarajevo. A total of 160 teeth were measured, of which 120 incisors and 40 canines. Examined dogs were classified by age, sex and length of the dental arch of the upper and lower jaw. Length of dental arch of the upper and lower jaws of German Shepherds is in range from 8 to 11.5 cm, with longer mandibular dental arch than the upper jaw. The differences in the dimensions of individual teeth between male and female German Shepherds were significant at p
Keywords: crown; frontal teeth; German Shepherd